COMPARISON OF SOFT TISSUE CHIN AND LOWER LIP THICKNESS IN ADULT PATIENTS WITH VARIOUS MANDIBULAR DIVERGENCE PATTERNS - Farooq, Ambar; Maimoona Afsar,; Khan, Verda Ahmad; Adil Shahnawaz,; Sardar Danial Hafeez,; Saima Shad,; Fatima Afsar, (Journal of Ayub Medical College Abbottabad, 2023)
Background: The influence of hard tissue discrepancies on the soft tissue cannot be ignored. The divergence or angle of the mandible can influence the lower lip and chin (soft tissue), similar to the influence of incisors inclinations on the pro/ retrusion of the lips. Hence this study was carried out to find out the impact of mandibular divergence patterns on contour and thickness of lower facial soft tissues. Methods: Using the Lateral cephalograms of 105 subjects, Lip thickness was measured between the protruding endpoint of the maxillary incisors (U1) to the stomion point (St) and between the infradentale (Id) and labrale inferius (Li). Soft tissue chin thickness was measured between the landmarks at hard tissue bony pogonion (Pog) to its opposite point on soft tissue (Pog'), hard tissue gnathion (Gn) to soft tissue gnathion (Gn') and hard tissue menton (Me) to its opposite point on ST menton (Me'). Results: Lower lip thickness from Id-Li (infradentale-labrale inferius) was greater in subjects with mandibular hyperdivergent pattern (p-value 0.097) while soft tissue chin thickness was decreased in hyperdivergent and increased in individuals with mandibular hypodivergence in both genders (p-value at gnathion was 0.596, menton was 0.023, and pogonion was 0.004, respectively). Conclusion: Lower lip thickness was increased in the individuals with mandibular hyperdivergence measured from infradentale to labrale inferius. While increased soft tissue thickness was observed at points gnathion and menton in patients with mandibular hypodivergence with no obvious difference at pogonion point.